1991
DOI: 10.1007/bf00918649
|View full text |Cite
|
Sign up to set email alerts
|

Repeated episodes of C5a-induced neutrophil influx do not result in pulmonary fibrosis

Abstract: Multiple reactive oxygen species-induced epithelial injury by glucose, glucose oxidase, and lactoperoxidase instillation in the lung results in a progressive interstitial fibrosis. To test the hypothesis that multiple pulmonary inflammatory responses alone would not result in fibrosis, three sequential inflammatory reactions were produced at weekly intervals in hamster lungs via intratracheal instillation of human recombinant C5a. Numbers of neutrophils and total inflammatory cells in bronchoalveolar lavage (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This peptide alone induces a brief inflammatory reaction and, as shown previously, this molecule does not induce long-term pulmonary changes [19]. In a more recent study, repeated instillation of a different chemoattractant, CSa, did not induce lung injury or lead to fibrosis [20].…”
Section: Discussionmentioning
confidence: 85%
“…This peptide alone induces a brief inflammatory reaction and, as shown previously, this molecule does not induce long-term pulmonary changes [19]. In a more recent study, repeated instillation of a different chemoattractant, CSa, did not induce lung injury or lead to fibrosis [20].…”
Section: Discussionmentioning
confidence: 85%
“…We have showed that reduction of neutrophil sequestration of BL treated lungs by application of nitroglycerin did not offer significant protection against BL induced lung fibrosis 56. Furthermore, repeated influx of neutrophils into the lung by intratracheal instillation of complement 5a failed to produce lung fibrosis 57. Thus, the status of lung inflammatory cells, especially the number of neutrophils, may not be directly related to the collagen level in BL induced lung fibrosis.…”
Section: Discussionmentioning
confidence: 92%
“…It has several proinflammatory effects which may lead to changes in blood flow and impairment of vascular integrity associated with oedema 6 . These effects are exerted by deliberation of enzymes, activation of effector mechanisms such as production of reactive oxygen species and rapid changes in expression of membrane molecules 7–10 …”
Section: Introductionmentioning
confidence: 99%